Clinical Case of Job Syndrome in Infant - Elena N. Alexeeva; Marina V. Besedina; Olga V. Zaytseva; Evgenia M. Tolstova; Niyra F. Benalieva (Педиатрическая фармакология)
The article presents clinical case of Job syndrome, variant of primary immune deficiency disease confirmed genetically. This case is interesting for its early diagnosis due to comprehensive assessment of anamnestic, clinical, and laboratory data. Such typical phenotypic features as facial dysmorphisms, recurrent localized purulent infections, and laboratory parameters (absolute neutropenia and eosinophilia) were the major signs of autosomal dominant hyper IgE syndrome in a child with normal IgE levels. The combination of 2 heterozygous mutations in STAT3 gene inherited from his father and his mother has played its role in disease clinical features in the child.